2016
DOI: 10.7863/ultra.15.05020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Malignancy in Hyperechoic Breast Lesions

Abstract: A hyperechoic breast lesion must not always be assumed to be benign. Instead, a full sonographic assessment according to the American College of Radiology Breast Imaging Reporting and Data System descriptors is needed for correct characterization and avoidance of misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
5
0
4
Order By: Relevance
“…5 lesions were palpable, 3 subjects had a previous history of carcinoma breast, 3 subjects had MRI correlation, 5 had mammography correlation, and vascularity was seen in 6 lesions. These results were in agreement with the results of Adrada B et al [8] in 2013 and Nassar L et al [9] in 2016 where the clinical evaluation of hyperechoic breast lesions showed similar results as the present study. The present study also assessed the sonographic aspects of the hyperechoic malignant lesions, it was seen that vascularity, hypoechoic lesions, shape, and posterior acoustic features were non-significant among benign and malignant hyperechoic lesions, whereas, circumscribed margins were seen in 62.5% (n=5) and non-circumscribed by 37,5% (n=3) study subjects with benign lesions, and by 100% (n=5) subjects with malignant lesions.…”
Section: Discussionsupporting
confidence: 94%
“…5 lesions were palpable, 3 subjects had a previous history of carcinoma breast, 3 subjects had MRI correlation, 5 had mammography correlation, and vascularity was seen in 6 lesions. These results were in agreement with the results of Adrada B et al [8] in 2013 and Nassar L et al [9] in 2016 where the clinical evaluation of hyperechoic breast lesions showed similar results as the present study. The present study also assessed the sonographic aspects of the hyperechoic malignant lesions, it was seen that vascularity, hypoechoic lesions, shape, and posterior acoustic features were non-significant among benign and malignant hyperechoic lesions, whereas, circumscribed margins were seen in 62.5% (n=5) and non-circumscribed by 37,5% (n=3) study subjects with benign lesions, and by 100% (n=5) subjects with malignant lesions.…”
Section: Discussionsupporting
confidence: 94%
“…Breast lesions described as hyperechoic are rare, making up only 0.2% to 0.6% of all lesions evaluated by US . Because many of these lesions are considered to be at low risk for malignancy by imaging criteria, fewer than half may undergo biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty to 65% of lesions described as “hyperechoic” by radiologists and undergoing biopsy also have areas that are not hyperechoic . This pattern is reported as “heterogeneous” in the BI‐RADS lexicon .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations